Israf dalam Ekonomi Digital: Perspektif Etika Konsumsi Islam terhadap Gaya Hidup Hedonis - Rahmi, Aulia; Moh Najib; Mesi Herawati; Harmanto Raharjo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
A hedonistic lifestyle that develops through social media and an algorithm-based digital system that encourages repeated consumption. This research aims to analyse how consumption practices in the digital economy can be categorised as isrāf and how Islamic consumption ethics can serve as an evaluative framework in responding to this phenomenon. This research uses a qualitative approach based on normative literature review with content analysis techniques and a hermeneutic approach. Data were obtained from scientific journal articles, academic books, as well as classical and contemporary Islamic literature from the period 2019–2025 that are relevant to digital consumption, hedonism, and Islamic consumption ethics. The research results show that digital consumption tends to be impulsive, symbolic, and influenced by algorithms, thus exceeding the limits of rational needs. This practice meets the characteristics of isrāf, both in terms of motives, patterns, and impacts. Furthermore, it was found that isrāf in the digital economy is not only individual in nature but is also influenced by social constructs and the structure of the digital system. This research concludes that Islamic consumption ethics, through the principle of moderation (wasathiyyah) and the framework of maqāṣid al-sharī‘ah, offer a relevant normative approach to controlling excessive consumption and building a more just and sustainable consumption pattern in the digital era.